Relationship Between Acute Appendicitis and Platelet Indices in Childhood - Asena Sucu; Orkun Tolunay; İlknur Banlı Cesur; Zerrin Özçelik; Tamer Çelik; Salim Reşitoğlu; Ümit Çelik (Journal of Pediatric Emergency and Intensive Care Medicine, 2018)
Introduction: Appendicitis is the inflammation of the appendix vermiformis. Clinical diagnosis of acute appendicitis in children is still a problem. Platelet indices, platelet distribution width and mean platelet volume have been evaluated for some infectious and inflammatory diseases. In this study, we aimed to investigate whether platelet distribution width values and mean platelet volume were decisive for the diagnosis of appendicitis in children.